Relevance of al-ṡaman al-‘adl on Modern Transaction - Wahida Sahir (Al-Kharaj: Journal of Islamic Economic and Business, 2021)
A perfectly competitive market can produce fair prices for sellers and buyers. If the market mechanism is disrupted, fair prices will not be reached. This study aims to determine the economic thought of Islamic Middle Ages (Al-Ghazali, Ibn Taymiyah and Ibn Khaldun), analyze the concept of demand and supply prices and the contribution of al-aman al-'adl in demand and supply prices according to Al-Ghazali, Ibn Taimiyah and Ibn Khaldun (Middle Ages). This research uses the method of library research with a historical, sociological and economic approach. Data sources used are primary data and secondary data.The results of this study indicate that Al-Ghazali was one of the thinkers of Islamic economics who initiated the concept of al-aman al-‘adl with a socialist style of thought. Ibn Taymiyyah was a cleric with a socialist mindset that was specifically focused on the market mechanism, emphasizing his views on the free market. Ibn Khaldun was the pioneer of the birth of sociology which summarized the discussion of history-philosophy and political economy. The style of Ibn Khaldun's economic thought is more directed to the style of socialist thought which strongly emphasizes the importance of a free market system. The concept of demand analysis is that the higher the price, the lower the demand will be. Meanwhile, the concept of supply analysis is the higher the price, the more number of goods offered. Al-ṡaman al-‘adl's contribution (fair price) according to Al-Ghazali addresses the issue of price and profit simultaneously without distinguishing between costs and income. The contribution of al-ṡaman al-‘adl (fair price) according to Ibn Taymiyyah maintains fairness in conducting reciprocal transactions and other relationships among members of the community, the concept of a fair price only occurs in competitive markets. The contribution of al-ṡaman al-‘adl (fair price) according to Ibn Khaldun is the price is very much determined by the demand and supply